Novel FOXF1 Deep Intronic Deletion Causes Lethal Lung Developmental Disorder, Alveolar Capillary Dysplasia with Misalignment of Pulmonary Veins. Issue 11 (4th September 2013) - Szafranski, Przemyslaw; Yang, Yaping; Nelson, Melissa U.; Bizzarro, Matthew J.; Morotti, Raffaella A.; Langston, Claire; Stankiewicz, Paweł
<x xml:space="preserve">Abstract</x> Haploinsufficiency of FOXF1 causes neonatal lethal Alveolar Capillary Dysplasia with Misalignment of Pulmonary Veins (ACDMPV). We report a novel pathogenic FOXF1 deep intronic deletion that did not affect major splicing sites. Results of the in vitro minigene‐based splicing and reporter assays performed in normal fetal lung fibroblasts suggest that the deletion likely compromised the intronic element(s) apparently regulating FOXF1 transcription. Our data further emphasize the importance of inclusion of non‐coding regions of the human genome in diagnostic testing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>